Philippine medical thesaurus on anatomy body regions in Bikol - Reblora, Ma. Aleth C., 1981- (Institute of Library and Information Science, University of the Philippines Diliman, 2004)
In answer to the pressing need for the information tool, a controlled vocabulary or authority list, the Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila teamed up into a collaborative effort to address this particular need. To meet this need, the project for establishing a multilingual Philippine Medical Thesaurus was launched and the first researches for the project were considered successful. As follow-up, another bilingual thesaurus, the Philippine Medical Thesaurus on anatomy: Body Regions in Bikol was done as an addition to the project.